2004
DOI: 10.1111/j.1572-0241.2004.04084.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Infected Ascitic Fluid Using Leukocyte Esterase Dipstick Testing

Abstract: The Multistix leukocyte esterase test is useful for the prompt detection of an elevated ascitic fluid PMN count, and represents a convenient new method for the rapid diagnosis of infected ascitic fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…24 Our study showed less sensitivity but high specificity and NPV ( Table 2). The result of our study was nearly similar to studies published by Butani et al and Ribeiro et al 14,20 Our study expands previous findings of the potential utility of the LERS test as a simple, rapid and inexpensive means for testing in settings involving SBP. If we compare two cut-offs ($++ and +++) used by us, both had performed fairly well for the diagnosis of SBP.…”
Section: Uriscansupporting
confidence: 82%
See 1 more Smart Citation
“…24 Our study showed less sensitivity but high specificity and NPV ( Table 2). The result of our study was nearly similar to studies published by Butani et al and Ribeiro et al 14,20 Our study expands previous findings of the potential utility of the LERS test as a simple, rapid and inexpensive means for testing in settings involving SBP. If we compare two cut-offs ($++ and +++) used by us, both had performed fairly well for the diagnosis of SBP.…”
Section: Uriscansupporting
confidence: 82%
“…Compared with the manual PMN count ('gold standard'), LERS were found to have sensitivity ranging from 45 to 100%, specificity ranging from 81 to 100%, PPV value ranging from 42 to 100% and NPV ranging from 87 to 100%. [4][5][6][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Similarly, the published studies in which Multistix reagent strips were used have also shown widely variable test results (Table 3). 4,[12][13][14][17][18][19][20]24 In an only study from India, authors have shown the Multistix strip's sensitivity, specificity, PPV and NPV of 97%, 89%, 87% and 83% respectively using a cut-off of grade 2.…”
Section: Uriscanmentioning
confidence: 99%
“…The first study [36] , published in 2002, involved 72 cirrhotic patients, nine of whom had SBP, reported a sensitivity and a specificity of 100% for the urinary strips in the diagnosis of SBP. After this successful result, in the following years a number of reports [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] evaluated the urine strip test for the diagnosis of SBP (Table 2). These studies reported promising and encouraging results, with the sensitivity of urinary strips for the diagnosis of SBP ranging between 85% and 100% and the specificity between 90 and 100%.…”
Section: The Determination Of Pmn Cells In the Ascitic Fluidmentioning
confidence: 99%
“…In these cases, some guidelines recommend antibiotic treatment only if the patient shows signs of infection [8] . Leukocyte reagent strips have been suggested as a rapid screening test for the diagnosis of SBP at the bedside [23][24][25][26] . However, sensitivity varying between 45% and 100%, makes this method suboptimal for the diagnosis of SBP.…”
Section: Diagnosis Of Spontaneous Bacterial Peritonitismentioning
confidence: 99%